Decolorization of methyl red using Bacillus thuringiensis RI16 strain: Enhanced bacterial treatment by SPB1 biosurfactant addition. Issue 12 (14th November 2022) - Mnif, Ines; Fendri, Raouia; Ghribi, Dhouha
Abstract: In this work, we evaluate the ability of a novel isolated bacteria identified as Bacillus thuringiensis RI16 (KM111604) to decolorize methyl red. Results showed its efficiency for the treatment of azo-dye-contaminated wastewaters under static conditions at pH values ranging from 7 to 9. The isolated bacteria could tolerate higher doses of dyes as it was able to decolorize up to 1000 mg/L. For better methyl red decolorization, we evaluate the potential use of Bacillus subtilis SPB1-derived lipopeptide biosurfactant. The study showed its ability to accelerate the decolorization rate and slightly maximized the decolorization efficiency at an optimal concentration of 0.025%. Compared with synthetic surfactants, the bacterial surfactant was more efficient as we observe a drastic decrease and an inhibition of methyl red decolorization by cetyl trimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS) additions. Also, studies ensured that methyl red removal by this strain could be due to extracellular enzymatic activities. SPB1 biosurfactant could improve enzyme activities and/or enzyme synthesis and diffusion. HIGHLIGHTS: B. thuringiensis RI16 for methyl red biodecolorization under static conditions and neutral and alkaline pH values. B. subtilis SPB1-derived lipopeptide-enhanced methyl red decolorization. Inhibition of methyl red decolorization by CTAB and SDS additions. Tween 80 enhanced methyl red decolorization. Improvement of color removal-related enzymes' activities and/or enzymes' synthesis and diffusion by SPB1 biosurfactant.